States versus markets the emergence of a global economy - Schwartz, Herman M. 1958- (Palgrave Macmillan, 2010)
"States versus Markets shows that globalization is not a novel phenomenon but a recurrent process whereby markets have, since the sixteenth century, periodically redistributed economic activity. This revised and updated new edition takes account of the new rise of Asia and the global financial crisis originating in the US housing finance system"--Provided by publisher.